PENGARUH INTRAVENA DRESSING TRANSPARAN TERHADAP KEJADIAN FLEBITIS: TINJAUAN SISTEMATIS - Wicke Afriza; Abdilah Septiana Putri; Yeni Astuti; Suci Rahmadia (Yayasan Nusantara Hasana Berdikari, 2024)
Phlebitis is a common complication of intravenous infusion. Several types of intravenous dressings have been reported to prevent phlebitis, but research results are still inconsistent. Objective: To systematically review the effect of using transparent dressings on the incidence of phlebitis in inpatients receiving intravenous therapy. Method: An article search was carried out in 3 databases, namely PubMed, Proquest and Google Scholar with the keywords